FINANCIAL COMPENSATION HAS A HUGE IMPACT TO NON-PERMANENT TEACHER’S (GTT) WORKING PRODUCTIVITY IN SMP N 2 JEMBER - Reni Dwi Agustina; Bagus P Yudhia K; Supardi Supardi (STIE Mandala Jember, 2018)
This article research entitled